Influence of Bioreceptor Layer Structure on Myelin Basic Protein Detection using Organic Field Effect Transistor‐Based Biosensors. (31st July 2018) - Song, Jian; Dailey, Jennifer; Li, Hui; Jang, Hyun‐June; Russell, Luisa; Zhang, Pengfei; Searson, Peter C.; Wang, Jeff Tza‐Huei; Everett, Allen D.; Katz, Howard E.
Abstract: Organic field‐effect transistor (OFET)‐based biosensors with antibody receptors are widely considered for protein antigen detection. To the authors' knowledge, there are no comparative evaluations to date of different choices for the matrix polymer to which the antibodies are attached. Herein, multiple acrylic copolymers are studied as receptor layers with myelin basic protein and its corresponding antibody as an archetypal antibody–antigen pair. Stability against multiple washing steps and the capacity for immobilizing antibodies on polymers on device surfaces with the help of fluorescein isothiocyanate‐labeled antibodies are compared. Electronic detection and selectivity are also observed. The conclusions provide guidance on the selection of bioreceptor material for increasing sensitivity and process stability of OFET biosensors. Abstract : Four COOH‐functionalized polymers are compared as matrices immobilizing antibody receptors for positively charged myelin basic protein (MBP). A higher COOH density increases antibody incorporation with the tradeoff of also promoting film dissolution. Polystyrene‐ co ‐methacrylic acid proved optimal, showing the highest electronic sensitivity in an MBP organic field‐effect transistor biosensor.